The Regenerative Lens: a conceptual framework for regenerative social-ecological systems - Buckton, Sam J.; Fazey, Ioan; Sharpe, Bill; Om, Eugyen Suzanne; Doherty, Bob; Ball, Peter; Denby, Katherine; Bryant, Maria; Lait, Rebecca; Bridle, Sarah; Cain, Michelle; Carmen, Esther; et al. (Elsevier, 2023)
Societies must transform their dynamics to support the flourishing of life. There is increasing interest in regeneration and regenerative practice as a solution, but also limited cohered understanding of what constitutes regenerative systems at social-ecological scales. In this perspective we present a conceptual, cross-disciplinary, and action-oriented regenerative systems framework, the Regenerative Lens, informed by a wide literature review. The framework emphasizes that regenerative systems maintain positive reinforcing cycles of wellbeing within and beyond themselves, especially between humans and wider nature, such that “life begets life.” We identify five key qualities needed in systems to encourage such dynamics: an ecological worldview embodied in human action; mutualism; high diversity; agency for humans and non-humans to act regeneratively; and continuous reflexivity. We apply the Lens to an envisioned future food system to illustrate its utility as a reflexive tool and for stretching ambition. We hope that the conceptual clarity provided here will aid the necessary acceleration of learning and action toward regenerative systems.
Keywords: regeneration; regenerative practice; transformation; social-ecological systems; sustainability; food systems; resilience; futures; evaluation; Three Horizons